The quartz-dioritic Hospitais intrusion (SW Iberian Massif) and its mafic microgranular enclaves – evidence for mineral clustering - Moita, Patrícia (2016)
The Hospitais pluton is an elliptical body, with its long axis orientedWNW–ESE, that belongs to the Évora Massif (Iberian Variscan belt). This intrusion has a quartz-dioritic composition, with plagioclase, quartz, amphibole (hornblende, but locally also cummingtonite) and biotite as the main mineral phases. Mafic microgranular enclaves in the quartz–diorite show the same minerals as the host, but with a greater abundance of amphibole and lower proportions of felsic minerals, especially quartz. U–Pb zircon ages obtained in one sample of the quartz–diorite and one sample of a mafic microgranular enclave gave identical ages, within error, of ca. 337 Ma. Geochemical data show that the quartz–diorite has a calc-alkaline signature with moderate enrichment in LILE/HFSE ratio (ThN/YN: 2.71–11.43) and clear negative Ti and Nb–Ta anomalies (ThN/NbN: 1.33–6.22). The composition of the enclaves shows that they do not represent direct melt compositions. Instead, their geochemical features (namely the abundances of Fe andMnin variation diagrams and REE patterns in primitive mantle normalized diagrams) suggest that they correspond to mineral clustering formed during the previous crystallization stage of quartz-dioritic magma. Overlapping of mineral chemistry and Sr–Nd isotope compositions in the quartz–diorite and the enclaves provides further support to that conclusion. The values for [87Sr/86Sr]i and εNdi (calculated for 337 Ma) in the quartz–diorite vary from 0.706147 to 0.706491 and from −1.87 to −3.22, respectively. This isotope composition may be explained either by differentiation of a mafic magma extracted from a mantle wedge enriched by long lasting subduction processes, or by mixing between a mafic magma from a depleted mantle source and a crustal melt. In the second case, the most likely source for the felsic component should be meta-igneous rocks, like the Lower Cambrian Alcáçovas orthogneisses that outcrop in neighbouring areas.